Color coding in the cortex: a modiﬁed approach to bottom-upvisual attention (2012)
Itti and Koch’s (Vision Research 40:1489–1506,2000) saliency-based visual attention model is a broadlyaccepted model that describes how attention processes aredeployed in the visual cortex in a pure bottom-up strategy.This work complements their model by modifying the colorfeature calculation. Evidence suggests that S-cone responsesare elicited in the same spatial distribution and have the samesign as responses to M-cone stimuli; these cells are tenta-tively referred to as red-cyan. For other cells, the S-coneinput seems to be aligned with the L-cone input; these cellsmight be green-magenta cells. To model red-cyan and green-magenta double-opponent cells, we implement a center-sur-round difference approach of the aforementioned model. Theresulting color maps elicited enhanced responses to colorsalient stimuli when compared to the classic ones at highstatistical significance levels. We also show that the modi-ﬁed model improves the prediction of locations attended byhuman viewers